Demographic Characteristics and Personal Hygiene Factors with Wound Healing in Patients with Cesarean Section - Nasirin, Chairun (International Journal of Psychosocial Rehabilitation, 2020)
A cesarean section is an incision in the uterine wall through the abdominal wall. Cesarean section occurs because of a history of previous cesarean section, fetal distress, HIV-positive status before birth, and narrow pelvis. In addition to wound healing, care for post-cesarean wounds is also necessary. Wound care is an action to prevent infection and accelerate wound healing. This study seeks to analyze the relationship between demographic characteristics and personal hygiene in cesarean postoperative patients at West Nusa Tenggara Provincial Hospital. The analysis shows that age is one of the factors that contribute to the response to wound healing. The results also showed that the level of education influences the individual in responding to wound healing. The next finding is that the level of work affects individuals in responding to wound healing. This is related to differences in work owned by someone causing differences in health status and what risks one must face.